Web Accessibility Evolution in the Brazilian Government - Oliveira, Alberto Dumont Alves; Freire, André Pimenta; Eler, Marcelo Medeiros (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2020)
The Brazilian Federal Government has published many pieces of legislation to assure the rights of people with disabilities with respect to both architectural and digital accessibility. Unfortunately, studies conducted in 2015 and 2017 have shown that the web portals of many federal agencies, including those with ministry status, failed to fully comply with the current legislation in many aspects. The aim of this paper is to re-evaluate the web portals of the Brazilian Federal Ministries to assess how much they evolved since 2015 concerning their compliance with the Brazilian Accessibility Model (e-MAG); usage of the Digital Government Identity; publication of the Circumstantial Report and Accessibility Work Plan; and usage of recommended Content Management Systems. The results of our evaluation show that compliance with the e-MAG standard with ratings based on the different types of guidelines violated slightly improved, but the number of instances of violations of guidelines significantly dropped; the usage of the Digital Government Identity has increased satisfactorily as well as the usage of recommended tools for developing and maintaining web portals; and only few web portals published the Circumstantial Report and Accessibility Work Plan.